2018
DOI: 10.1128/jvi.01948-17
|View full text |Cite
|
Sign up to set email alerts
|

Parainfluenza Virus Infection Sensitizes Cancer Cells to DNA-Damaging Agents: Implications for Oncolytic Virus Therapy

Abstract: A parainfluenza virus 5 (PIV5) with mutations in the P/V gene (P/V-CPI) is restricted for spread in normal cells but not in cancer cells and is effective at reducing tumor burdens in mouse model systems. Here we show that P/V-CPI infection of HEp-2 human laryngeal cancer cells results in the majority of the cells dying, but unexpectedly, over time, there is an emergence of a population of cells that survive as P/V-CPI persistently infected (PI) cells. P/V-CPI PI cells had elevated levels of basal caspase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 64 publications
4
13
0
Order By: Relevance
“…DNase I treatment conditions (15 U, 35 minutes at room temperature) used in this study resulted in DAPI‐stained nuclei in some cells. This result is comparable with other studies using similar DNase treatment conditions (Fox, Parks, & Dutch, ; Lebon et al, ; Zhang et al, ).…”
Section: Resultssupporting
confidence: 92%
“…DNase I treatment conditions (15 U, 35 minutes at room temperature) used in this study resulted in DAPI‐stained nuclei in some cells. This result is comparable with other studies using similar DNase treatment conditions (Fox, Parks, & Dutch, ; Lebon et al, ; Zhang et al, ).…”
Section: Resultssupporting
confidence: 92%
“…While at this point it is unclear how HDAC inhibitors promote P/V-CPI-medicated increases in caspases, there is a potential mechanism linked to scriptaid-induced decreases in cellular inhibitors of apoptosis. This is supported by our previous findings that expression of cIAP-1, XIAP, and survivin are all decreased by P/V-CPI- infection and that chemical inhibition of survivin (with YM155) or XIAP (with Embelin) enhanced killing of a P/V-CPI- persistently infected cell line [26].…”
Section: Discussionsupporting
confidence: 82%
“…We have previously shown that infection with the cytoplasmic-replicating RNA virus P/V-CPI-can sensitize airway cancer cells to chemotherapeutic DNA damaging agents through the modulation of DNA damage response pathways [26]. This prior finding led us to test the hypothesis that P/V-CPI- infection would also sensitize cancer cells to treatment with other chemotherapeutic agents that alter gene expression, DNA metabolism and stress responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired DNA repair machinery is likely to increase cancer cell killing by DNA-damaging chemotherapeutic drugs [50,51]. Therefore, we explored the possibility that U94 might act as a chemo-sensitizer molecule.…”
Section: Resultsmentioning
confidence: 99%